(untitled) (Balneo and PRM Research Journal, 2024)
Mangalia balneary resort is situated in the south of the Black Sea and uses sulphurous water springs for rehabilitation therapy. The purpose of this study is to demonstrate the effectiveness of Mangalia sulphurous water on Helicobacter Pylori (H. Pylori) infection. Considering that sulfurous water has a bacteriostatic effect and that most gastritis are caused by H. Pylori infection, we propose that a group of 27 H. Pylori positive patients with or without digestive symptoms ingest sulfurous water daily, for a few days. At the end of the study, 15 of the patients tested negative for H pylori antigen. The curative effects are due to the bacteriostatic effect of sulfurous water and its stimulating action on the digestive tube.